Implementation of Load Balancing of Two PCC-Based Internet Interconnections on Mikrotik Routers - Syukron Ma’mun; Muhajir Syamsu; Vany Terisia (International Journal of Technology and Education Research, 2026)
The increasing need for reliable internet connectivity requires organizations to optimize network performance and availability. PT Solusi Integra Datakom uses two internet service providers (ISPs), but bandwidth utilization is not optimal because it still implements manual failover. This study aims to implement Per Connection Classifier (PCC)-based load balancing on MikroTik routers and evaluate its impact on network performance. The study uses a quantitative approach with an experimental method and a one-group pretest-posttest design. The study population is all data traffic passing through the company's dual-ISP network, while the sample is data from network performance measurements before and after PCC implementation selected using purposive sampling. The research instruments include MikroTik routers, two ISP connections, client devices, and the NPerf application. Data were analyzed using comparative descriptive analysis based on Quality of Service (QoS) parameters, namely throughput, latency, and jitter. The results show that download throughput increased from 30.73 Mbps to 94.80 Mbps and upload throughput increased from 6.02 Mbps to 81.56 Mbps. Additionally, latency decreased from 28 ms to 10 ms, and jitter decreased from 9 ms to 5 ms. Failover testing also demonstrated that connectivity remained stable even when one of the ISPs experienced an outage. In conclusion, the PCC method effectively improves bandwidth utilization, network stability, and service availability in a dual-ISP environment